Mental Health and Psychological Adaptability on Hybrid Learning Set-Up of Criminology Students - Barnuevo, Nanies (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the mental health status and psychological adaptability of criminology students in a hybrid learning set-up in the First District of Camarines Sur during Academic Year 2022–2023. It aimed to assess students’ mental health status in terms of stress, anxiety, and depression; determine their level of psychological adaptability; examine the relationships between demographic characteristics, mental health status, and psychological adaptability; and propose an intervention program to improve students’ psychological adaptability toward mental health. The study was anchored on the Theory of Student Mental Health, Metacognitive Theory, and Behavioral Learning Theory. A descriptive-correlational research design was employed, involving 329 criminology students from first year to fourth year of two institutions in the First District of Camarines Sur. Respondents were selected through simple random sampling using the Yamane sample size formula (Yamane, 1967). Data were gathered using a researcher-made survey questionnaire and analyzed through frequency count, percentage technique, weighted mean, and Pearson Product Moment Correlation. The findings revealed that criminology students experienced moderate levels of stress, anxiety, and depression. Students demonstrated moderately high psychological adaptability in managing these challenges. Results showed that some demographic variables had significant relationships with specific mental health dimensions, while relationships between mental health status and psychological adaptability varied across indicators. An intervention program was proposed to strengthen mental health awareness and psychological adaptability among students. The study contributes to Sustainable Development Goal 3 (Good Health and Well-Being) and Sustainable Development Goal 4 (Quality Education) by supporting learning environments. Its sustainability impact focuses on educational and institutional sustainability.